Palestina Vs Israel Studi Kritis Tentang Kejahatan Perang dan Yurisdiksi Internasional - Asathin, Sifa Alfyyah; Nafisa'ah, Salsabila (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This study examines Palestine’s claims against Israel for war crimes through the International Criminal Court (ICC). The prolonged conflict between Israel and Palestine has resulted in numerous violations of international humanitarian law, including war crimes, crimes against humanity, and human rights violations. This study aims to analyze the legal basis for Palestine’s claims and ICC’s jurisdiction in prosecuting Israel, given that Israel is not a party to the Rome Statute. The research employs a document analysis method, examining various sources of international law, official reports, and ICC rulings on similar cases. The findings reveal that Palestine has met the requirements to be a state party to the Rome Statute since 2015, enabling it to file claims against Israel. Although Israel is not an ICC member, the Court can exercise jurisdiction since the alleged crimes occurred in Palestinian territory, which has accepted ICC’s authority. This study also identifies various war crimes committed by Israel, including attacks on civilians, the use of prohibited weapons, and obstruction of humanitarian aid. Thus, the findings highlight the urgency of ICC’s involvement in prosecuting this case to uphold international law and provide justice for the victims of the conflict.